ANALISIS PENGARUH KOMPENSASI DAN IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN PT. CAHAYA ANUGERAH BAHARI MEDAN - Robin Zheng; Silvia Sofyan Sofyan; Desy Angkasa Angkasa; Mianda Amoria Br Ginting Br Ginting (JEBIM Prima, 2022)
This study aims to determine the effect of compensation and organizational climate on the performance of employees of PT. The Light of the Medan Maritime Award. Methods of collecting data with a questionnaire. The questionnaire was tested for validity and reliability before collecting research data. The data analysis technique in this study used the classical assumption test and multiple linear regression analysis. The results showed that compensation partially has a positive and significant effect on purchasing decisions. This is evidenced by the tcount of 3.609 > from ttable of 2.034 and a significant value below 0.05, which is 0.001. While the organizational climate partially positive and significant effect on purchasing decisions. This is evidenced by the tcount of 2.648 > from ttable of 2.034 and a significant value below 0.05, which is 0.012. Simultaneously, compensation and organizational climate have a positive and significant effect on purchasing decisions. This is evidenced by Fcount of 15,039 > from Ftable of 3.28 and a significant value below 0.05, which is 0.000. The magnitude of the influence given is 47.7% while the rest is influenced by other factors outside of this study.